Analisis Kemampuan Numerik Siswa Kelas V dalam Mengerjakan Soal Tipe Higher Order of Thinking Skill - NurBerlianty Silalahi; Deri Hendriawan (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
Numerical ability is the ability possessed by humans to understand, apply, and interpret mathematics in different forms. This ability is also included in a person's high-level reasoning ability and ability in a problem related to numbers. The purpose of this study was to identify the numerical abilities of fifth grade students by conducting a trial test with questions of the higher order of thinking skill (HOTS) type. The research used is qualitative with content analysis method. The research subjects were fifth grade students consisting of 35 students at SDN Lilang. Data collection techniques were carried out by interviews, observation and trial tests. The results showed that the numerical ability of students has a percentage of 53.33% of students in the medium ability group and 46.67% of students in the low ability group.